Academic education in health marketing in Ibero-America - Nery Suárez Lugo (Horizonte Sanitario, 2017)
Objective: Identify the academic education modality offerings in health marketing in Ibero-America. Materials and methods: Descriptive observational research. Questionnaire by email, online documental review. Universe made up of representativesof the Ibero-American Health Marketing Network (henceforth referred to by its Spanish acronym RIMS) and teachers involved with the subject in20 Ibero-American countries in 2015; non-probability convenience sampling used. The questionnaire was answered in 17 countries. The summarizedinformation is presented in absolute frequencies and percentages. Results: In all of the countries that answered the questionnaire, some form of health marketing modality is offered. "Lack of understanding of the needto offer various modalities to train health professionals and managers in marketing" was given as the main reason for its absence in academic educationin health sciences. Most of the countries (82.4 %) state that they have teachers trained in the subject. The modalities most offered are: master’s degreesubject (24.39 %), courses (19.5 %) and diplomas (17.07 %).Conclusions: Insufficient supply of academic education offerings in health marketing and a lack of dissemination of existing ones is a commondenominator to all countries, coupled with a lack of understanding in the public sector of the need to train health professionals in marketing.